(untitled) (Medical Forum Monthly, 2021)
Objective: To find out the impact of COVID-19 on teaching and learning in medial institutes of Sialkot and to indentify the need of communication skills, decision making, problem solving and improving learning assessment outcomes in students. Study Design: Prospective cohort study Place and Duration of Study: This study was conducted at the medical institutes of Sialkot from January 2021 to August, 2021 for a period of 08 months. Materials and Methods: Total 50 professionals of various designations from professors to Senior Registrar of 03 medical institutions namely Khawaja Muhammad Safdar Medical College Sialkot, Islam Medical college Sialkot, Sialkot Medical College were including in the study. Results: Conclusion: The impact of COVID-19 on teaching and learning process affects globally, nationally and regionally. The results are to be determined in order to find out barrier in teaching and learning process. The study issues can be resolved by experienced quality instructors, student interest, effective curriculum design and uninterrupted online tutorials.